Explaining the forms of generation Z’s political engagement: A study on generation Z in Semarang, Indonesia - Muhammad Zulfa Alfaruqy; Anandaru Padmonurcahyo; Adinda Zahrah Salsabila (Universitas Trunojoyo Madura, 2022)
This study aimed to construct the form of political engagement and examine the differences in any political engagement in Generation Z based on age, gender, and scientific field. This study involved 600 Generation Z (300 male, 300 female) who were studying at Universitas Diponegoro, Semarang, Indonesia. This study uses a mixed method consisting of qualitative grounded theory and quantitative comparison. Data collection uses open-ended questions, in depth interview, and a political engagement scale (16 items; = 0.862). The results show that the form of political engagement of Generation Z includes the cognitive type such as understanding and analyzing political conditions, and the behavior type such as voting, expressing opinions, and habituating socio-political values in daily life as good citizens. Forms of political involvement vary from individual to collective. Generation Z’s political perception cannot be separated from the results of social construction by online media and significant others. There are differences in the political engagement of Generation Z on age and scientific field. However, there is no difference in political engagement related to gender. This research has implications for the urgency of the functioning of social systems that ensure the exposure of reliable information and provide space for expression for Generation Z to be involved in the political arena.